Karyological investigations of Caryophyllaeus laticeps (Pallas, 1781) (Cestoda: Caryophyllidea) - Petkeviciute, R; Kuperman, B I (Folia parasitologica, 1992)
Mitotic and meiotic chromosomes of Caryophyllaeus laticeps (Pallas) from Rybinsk reservoir were studied using air-drying techniques. It was established that the diploid set contains 20 metacentric chromosomes. The chromosomes are large--their mean absolute length ranges from 3.00 to 12.90 microns. The last pair of small homologues comprises only 3.4% of the total length of the complement. One specimen of C. laticeps with 2n = 21 (trisomic after the last pair of chromosomes) and one triploid specimen with 3n = 31 is described. Data on the comparative karyology of caryophyllids are discussed.
Keywords: Chromosomes; nemoci ryb; Cestode Infections; Metaphase; Fish Diseases; mitóza; Meiosis; zvířata; metafáze; meióza; Ploidies; ploidie; cestodózy; chromozomy; Mitosis; karyometrie; Animals; Karyometry; Cestoda; Cyprinidae